Bis‐Thioether‐Containing Lipid Chains in Cationic Amphiphiles: Physicochemical Properties and Applications in Gene Delivery. Issue 17 (8th August 2019) - Bouraoui, Amal; Ghanem, Rosy; Berchel, Mathieu; Vié, Véronique; Le Guen, Yann; Paboeuf, Gilles; Deschamps, Laure; Le Gall, Tony; Montier, Tristan; Jaffrès, Paul‐Alain
Abstract: Cationic amphiphiles featuring two thioether functions in each lipid chain of bicatenar cationic amphiphiles are reported here for the first time. The physicochemical properties and transfection abilities of these new amphiphiles were compared with those of already reported analogues featuring either (i) saturated, (ii) unsaturated or (iii) mono‐thioether containing lipid chains. The homogeneity of the series of new compounds allowed to clearly underscore the effect of bis‐thioether containing lipid chains. This study shows that besides previous strategies based on unsaturation or ramification, the incorporation of two thioether functions per lipid chain constitutes an original complementary alternative to tune the supramolecular properties of amphiphilic compounds. The potential of this strategy was evaluated in the context of gene delivery and report that two cationic amphiphiles (i. e.4 a and4 b) can be proposed as new efficient transfection reagents. Abstract : New lipid chains containing two thioether functions are incorporated in the structure of cationic amphiphiles. Physicochemical studies underscore both the fluidity and adaptability of these lipid chains to lateral pressure. The cationic lipids are assessed as in vitro synthetic gene carriers.